Oscillation of Third Order Quasilinear Advanced Differential Equation with ``Maxima - G. Ayyappan; P. Gayathri; V. Mahadevan (International Journal of Mathematics And its Applications, 2018)
This paper study the asymptotic properties of third order advanced differential equation with ``maxima'' of the form $$\left(a(t)(x''(t))^\gamma \right)'+q(t)\max_{[t, \tau(t)]}x^\gamma(s)=0,~~t\geq t_0,$$ where $\gamma$ is ratio of odd positive integers. Give an example to illustrate the main results.